Cellobiose dehydrogenase: Insights on the nanostructuration of electrodes for improved development of biosensors and biofuel cells. (December 2017) - Bollella, Paolo; Ludwig, Roland; Gorton, Lo
Graphical abstract: Abstract: Cellobiose dehydrogenase (CDH) is a versatile bioelectrocatalyst lately at focus due to its sugar oxidising properties in combination with its inherent ability for direct electron transfer communication with electrodes making it possible to be used in bioanodes in the enzymatic fuel cells (EFCs), self-powered biosensors, and biosupercapacitors. During the last 20 years, many new nanomaterials and hybrid nanocomposites have been developed and employed in combination with various oxidoreductases, such as CDH, to increase the overall performance of electrical devices (e.g. biosensors, EFCs etc.). It has also been shown that nanomaterials can be further chemically modified to facilitate electron transfer pathways between the biocomponent and electrodes. Both carbon and metal based nanomaterials and combinations thereof have been used together with CDH to improve the performance. In this review, we resume all the findings related to the influence of effective nanostructuration to improve the electron transfer communication with electrodes yielding higher sensitivity of biosensors or increasing the power output of EFC based on CDH from different sources.